(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
It is impossible to literally translate proverbs, which are oral works of the people. Correctly translating a proverb requires several steps and often requires the translator to study the culture of the source and target languages in depth to determine the idiomatic translation. In this article, broad recommendations on the translation of proverbs are given and analyzed with examples.